Factors Influencing Academic Performance, With the Mediating Role of Knowledge Sharing of Students: Evidence from Public Higher Education Institutions in Vietnam - Yen, Tran Hai; Linh, Nguyen Phuong; Quyet, Phan Dinh (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this paper is to investigate Vietnamese students' perceptions in terms of the influence of factors on academic performance through knowledge sharing. A quantitative research approach was used in this study. The Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach supported by Smart-PLS 3.0 computer software was used for data analysis. An online questionnaire was distributed to 289 participants, but only 250 qualified. The participants in this study were Vietnamese students who are studying at public universities in Vietnam. This pilot study indicates that all factors, including knowledge self-efficacy; university support, information technology were found to be significant predictors of sharing activities. Furthermore, knowledge sharing has a positive impact on their academic performance. Among this, knowledge self-efficacy has the strongest impact on knowledge sharing, meanwhile, information technology has the least impact on knowledge sharing.